Ex vivo normothermic porcine pancreas: A physiological model for preservation and transplant study. (June 2018) - Kumar, Rohan; Chung, Wen Yuan; Runau, Franscois; Isherwood, John David; Kuan, Kean Guan; West, Kevin; Garcea, Giuseppe; Dennison, Ashley Robert
Abstract: Introduction: An ex vivo normothermic porcine pancreas perfusion (ENPPP) model was established to investigate effects of machine perfusion pressures on graft preservation. Methodology: Nine porcine pancreata were perfused with autologous blood at 50 mmHg (control) pressure. Graft viability was compared against four ex-vivo porcine pancreata perfused at 20 mmHg ('low') pressure. Arterio-venous oxygen gas differentials, biochemistry, and graft insulin responses to glucose stimulation were compared. Immunohistochemistry stains compared the cellular viability. Results: Control pancreata were perfused for a median of 3 h (range 2–4 h) with a mean pressure 50 mmHg and graft flow 141 mL min −1 . In comparison, all of the 'low' pressure models were perfused for 4 h, with mean perfusion pressure 20 mmHg and graft flow 40 mL.min-1. All pancreata demonstrated cellular viability with evidence of oxygen consumption with preserved endocrine and exocrine function. However, following statistical analysis, the 'low' pressure perfusion of porcine pancreata compared favourably in important biochemical and immunohistochemistry cellular profiles; potentially arguing for an improved method for graft preservation. Conclusion: ENPPP will facilitate whole organ preservation to be studied in further detail and avoids use of expensive live animals. ENPPP is reproducible and mimics a "donation after circulatory death" scenario. Highlights: The world's first physiological ex vivo porcine pancreas model has been established. It is suitably reliable to investigate effects of machine perfusion parameters on graft preservation. We have successfully used it to compare to perfusion pressures for graft preservation. This porcine pancreas ex vivo model avoids use of expensive live animals. It is reproducible and mimics a "donation after circulatory death" scenario.